Subtrigging as alternatives through regularities - Jayez, Jacques; Tovena, Lucia (Proceedings of the Amsterdam Colloquium, 2007)
In this paper, we work out the connection between the well-known phenomenon of subtrigging for F(ree) C(hoice) I(tems) and the widespread intuition that these items exploit alternatives, by showing that the missing link is the notion of regularity.